Arbuscular mycorrhizal fungi improve the growth and drought tolerance of Cinnamomum migao by enhancing physio‐biochemical responses. Issue 7 (11th July 2022) - Yan, Qiuxiao; Li, Xiangying; Xiao, Xuefeng; Chen, Jingzhong; Liu, Jiming; Lin, Changhu; Guan, Ruiting; Wang, Daoping
Abstract: Drought is the main limiting factor for plant growth in karst areas with a fragile ecological environment. Cinnamomum migao H.W. Li is an endemic medicinal woody plant present in the karst areas of southwestern China, and it is endangered due to poor drought tolerance. Arbuscular mycorrhizal fungi (AMF) are known to enhance the drought tolerance of plants. However, few studies have examined the contribution of AMF in improving the drought tolerance of C. migao seedlings. Therefore, we conducted a series of experiments to determine whether a single inoculation and coinoculation of AMF ( Claroideoglomus lamellosum and Claroideoglomus etunicatum ) enhanced the drought tolerance of C. migao . Furthermore, we compared the effects of single inoculation and coinoculation with different inoculum sizes (20, 40, 60, and 100 g; four replicates per treatment) on mycorrhizal colonization rate, plant growth, photosynthetic parameters, antioxidant enzyme activity, and malondialdehyde (MDA) and osmoregulatory substance contents. The results showed that compared with nonmycorrhizal plants, AMF colonization significantly improved plant growing status; net photosynthetic rate; superoxide dismutase, catalase, and peroxidase activities; and soluble sugar, soluble protein, and proline contents. Furthermore, AMF colonization increased relative water content and reduced MDA content in cells. These combined cumulative effects of AMF symbiosis ultimately enhanced the drought tolerance of seedlings and were closely related to the inoculum size. With an increase in inoculum size, the growth rate and drought tolerance of plants first increased and then decreased. The damage caused by drought stress could be reduced by inoculating 40–60 g of AMF, and the effect of coinoculation was significantly better than that of single inoculation at 60 g of AMF, while the effect was opposite at 40 g of AMF. Additionally, the interaction between AMF and inoculum sizes had a significant effect on drought tolerance. In conclusion, the inoculation of the AMF ( Cl. lamellosum and Cl. etunicatum ) improved photosynthesis, activated antioxidant enzymes, regulated cell osmotic state, and enhanced the drought tolerance of C. migao, enabling its growth in fragile ecological environments. Abstract : The presence of AM fungi, Claroideoglomus etunicatum and Claroideoglomus lamellosum, improved the drought tolerance of Cinnamomum migao by increasing photosynthetic parameters, antioxidant enzyme activities, and osmosis‐regulating substances. In addition, the interaction between AMF and inoculum sizes had an obvious effect on drought tolerance. The results of this study supported the drought‐resistant mechanism of C. migao mediated by AMF.